Optimizing Tax Revenue Growth: An Analysis of the Role of Self Assessment System and VAT Restitution at KPP Pratama Cirebon One Year (2020-2023) - Azharul Balighin; Sri Revalina Ningsih; Asep Basuki (Cita Konsultindo Research Center, 2024)
This research aims to analyze whether VAT revenues can be influenced by the self-assessment system with VAT refunds at KPP Pratama Cirebon Satu. The data collection method designed by the researcher uses data analysis methods from direct sources from the Cirebon Satu KPP Pratama report. The study was carried out using a purposive sampling method. This research was tested using multiple linear regression analysis. This research uses secondary data by taking the total population at KPP Pratama Cirebon Satu with a mandatory sample of 46 data at KPP Pratama Cirebon Satu. This test tool was analyzed using the IBM SPSS Statistics 25 application. The results of data analysis for this research explain that the Self assessment system has an impact on VAT revenue. On the other hand, VAT Restitution affects VAT Revenue